An approach for automated detection of missing reagents and products in chemical reaction equations - R.I. Nugmanov; T.I. Madzhidov; I.S. Antipin; A.A. Varnek (Учёные записки Казанского университета: Серия Естественные науки, 2018)
One of the problems of chemical reactions databases management is the fact that most reactions in them are stoichiometrically unbalanced, i.e., they lack information about one or more reagents or products. It leads to the problem that some reactions cannot be found in structural searches. A solution of the problem based on the use of the Condensed Graph of Reaction (CGR) approach has been suggested. The CGR is a compressed representation of the reaction transformation in which the atoms of the reagent and the product are aligned. As a result, so-called dynamic bonds corresponding to changes in the bond order during the chemical transformation are identified in the pseudomolecular graph along with the usual chemical bonds. The key observation is that the Condensed Graph, on the one hand, contains all required structural information on chemical reaction and, on the other hand, can be constructed for an unbalanced chemical reaction with missing reagents or products. During the inverse transformation of the Condensed Graph into a chemical reaction, the information on the missing reagents and products can be restored. There are some limitations to this approach, because information about coefficients missing in the reaction cannot be retrieved by the proposed method. To solve such problems, an algorithm based on the use of isomorphic embedding has been developed. This algorithm reveals similar motifs in the Condensed Graph and, if necessary, adds a coefficient before the reagent and/or product, or copies them the required number of times in the reaction equation.